Competitiveness in Banking Sector: A Systematic Literature Review - Begimkulov, Emil (Marketing & Menedzsment, 2023)
THE AIMS OF THE PAPER The current paper explores the directions and trends of research on the concept of banking system competition by reviewing published scientific articles. Based on the results, it provides scientific and practical implications. METHODOLOGY The research follows the systematic literature review method. First, a set of keywords were defined. Then, the keywords were used to identify articles in Web of Science and Scopus. The identified articles were filtered and screened following the PRISMA method of selection. At the final stage, 61 articles were included. MOST IMPORTANT RESULTS Based on the analysis of scientific literature, the study identified the main research streams on bank competition: risk-stability, market power, macroeconomic context, bank activities, new approaches, and digitalization. At the same time, there exist significant inconsistencies in scholarly findings on the relationship between competition and research streams. RECOMMENDATIONS Based on the findings, the article proposes conceptual and practical implications. Scientists should consider the existing mixed effects of competition on research streams. Policymakers, bank owners, and managers can utilize the synthesized results of the study to improve bank competitiveness and performance based on different competitive scenarios.